Roadmaps Classification - P. Loginov, Mikhail; P. Ivanitsky, Victor; S. Maramygin, Maksim; A. Tatyann, Vasiliy (International Journal of Engineering and Technology, 2018)
Creating modern maps is one of the methods for simplifying business and improving logistics. This research systematizes the main methods for making ties, object mapping, Ob-EKT planning, specific types of road maps and their features. Different roadmaps are systematized in four types: public, corporate, thematic (expert) and the project roadmaps (project/program/portfolio management plan). We introduce an original approach to identifying the road map maturity level. There are four maturity levels: network, expert opinion, the concept (strategy), management plan.Â Â